HUMAN RIGHTS AND LABOR LAW - Stürmer, Gilberto (Novos Estudos Jurídicos, 2019)
This text addresses the right to work, and labor law based on the Protocol of San Salvador, which is part of the American Convention on Human Rights, also called the Pact of San José, Costa Rica. The aims of Labor and labor legislation within the scope of human rights, and also in Brazilian constitutional system as part of the fundamental rights and guarantees, is to achieve a Democratic State of Law and social justice, which are the basis of a fair and fraternal society. This investigation is linked to positive or negative social impact of the regulations on the right to work and labor law, both within the domestic legal system (such as rights and fundamental principles), and internationally, as human rights (especially in the Protocol of San Salvador). This work therefore aims to demonstrate that the regulation of the right to work and labor law is part of a broad social context of rights.